1985
DOI: 10.1115/1.3261041
|View full text |Cite
|
Sign up to set email alerts
|

An Adiabatic Solution of Misaligned Journal Bearings

Abstract: The paper presents an adiabatic analysis of misaligned journal bearings. The misalignment is allowed to vary in magnitude as well as in direction with respect to the bearing boundaries. Results are obtained for the case of a fixed journal axis with a bearing length to diameter ratio of unity. It is concluded that thermal effects are more pronounced for misaligned journal bearings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…For a misaligned bearing, the different crosssection along the axis of bearing has different location of journal centre. Therefore, e and c in equation (2) are the function of y coordinate and can be given by…”
Section: Film Thicknessmentioning
confidence: 99%
“…For a misaligned bearing, the different crosssection along the axis of bearing has different location of journal centre. Therefore, e and c in equation (2) are the function of y coordinate and can be given by…”
Section: Film Thicknessmentioning
confidence: 99%
“…Mokhtar et al [83] in 1985 obtained an adiabatic solution for a misaligned journal bearing. They showed that the misalignment effects on the bearing performances are more significant when thermal effects are considered, as expected.…”
Section: Thermal Effectsmentioning
confidence: 99%
“…Nicholas (1972) estableció que la intensidad del par producido por el desalineamiento induce poca influencia sobre la excentricidad y la rapidez del flujo axial, pero que la presión máxima se incrementa significativamente. Mokhtar et al, (1985) hacen una evaluación de las características térmicas en chumaceras desalineadas usando un enfoque adiabático. Buckholz y Lin (1986) analizaron el efecto del desalineamiento y la cavitación en chumaceras parciales lubricadas con fluidos No-Newtonianos.…”
Section: Introductionunclassified